RANCANG BANGUN SISTEM INFORMASI PENERIMAAN KAS LAYANAN TINDAKAN MEDIS PUSKESMAS BOTANIA BATAM KOTA - Elisa, Erlin; Tukino, Tukino; Amrizal, Amrizal (Universitas Putera Batam, 2022)
Public health centers play a crucial role as frontline healthcare service providers, dedicated to enhancing the well-being of their communities. Ensuring the delivery of the best possible services is a primary responsibility. However, one significant challenge they face is the manual recording of general medical services, making the process susceptible to transaction recording errors. This study's objective is to develop an analysis and design for a cash receipt application tailored to medical action services, addressing this issue. To achieve this goal, the research employs various methods, including data collection through interviews and documentation techniques. The current system is thoroughly analyzed, identifying its shortcomings and areas for improvement. Additionally, the Unified Modeling Language (UML) is employed to create a comprehensive design for the proposed cash receipt application. The outcome of this study is a well-crafted design for a medical action service cash receipt application. This application has the potential to streamline the process, reduce errors, and enhance the overall efficiency of health center operations. Implementing this system could significantly contribute to the improvement of healthcare services in the community, ultimately benefitting the public's health and well-being.